Pilot Program Pengembangan Desa Wisata Berwawasan Lingkungan dan Kearifan Lokal di Desa Kuripansari, Kabupaten Mojokerto: Pilot Program for the Development of Environmentally Conscious and Locally-Inspired Tourism Village in Kuripansari Village, Mojokerto Regency - Rumayya, Rumayya; Rahayu, Titik Puji; Nindya, Triska Susila; Prameswari, Zendy Wulan Ayu Widhi; Akhsani, Onish (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Kuripansari Village, situated on the slopes of Mount Arjuno, possesses significant natural and cultural potential for development as an environmentally based tourism village rooted in local wisdom. However, its development has not yet been carried out in a structured and contextually appropriate manner. Through a community service initiative, a series of awareness-building and village potential mapping activities were conducted using a participatory and educational approach to foster public engagement in shaping the direction of tourism development. The program featured speakers from local communities and village youth, who presented materials on tourism management, the nutritional value of wild edible plants, and community empowerment. The results indicated a high level of enthusiasm among participants and growing awareness of the village's unique assets, particularly in developing educational tourism based on the use of wild plants. In addition to the outreach activities, a greenhouse facility was established to support both cultivation and education. This initiative serves as a foundational step toward developing a contextual, sustainable, and community-driven tourism model.